Coronary artery dilation associated with anti-synthetase syndrome in an adolescent - Karim Asi; Anand Gourishankar; Ankur Kamdar (BMC, 2019)
Abstract Background Idiopathic inflammatory myopathies (IIM) are a group of systemic autoimmune disorders primarily affecting skeletal muscle. Pediatric coronary artery dilation is frequently discussed in Kawasaki disease. However, it has yet to be reported in the IIMs or antisynthetase syndrome. We report a unique case of a patient with IIM, antisynthetase syndrome and coronary artery dilation. Case presentation We report an adolescent presenting with joint symptoms, fever, and eye swelling with a clinical diagnosis of Juvenile Dermatomyositis. He subsequently developed diastolic hypotension with evidence of coronary artery dilation. He received steroids and immunoglobulin and followed by immunosuppressants with mild improvement in his symptoms. The adolescent later developed dyspnea and cough with CT lungs evident for cystic changes; lung biopsy showed interstitial fibrosis and inflammation, and muscle biopsy was abnormal as well. The anti-pl-12 antibody was positive. Following several weeks of treatment, an echocardiogram showed improvement in coronary artery dilation. His joint symptoms, muscle strength and respiratory symptoms have also improved. Conclusions Coronary artery dilation is not well understood in IIMs or antisynthetase syndrome. Pathobiology of coronary artery involvement, its treatment and prognosis, and association with IIM and antisynthetase syndrome needs further exploration.